Le développement de carrière des jeunes filles à la fin des études secondaires - Dupont, Pierrette; Gingras, Marcelle (Canadian Journal of Counselling and Psychotherapy, 2011)
This article examines the career development of teenage girls who have reached the stage of vocational exploration. We first compare the academic and professional choices available to girls and boys at the end of their secondary school program. We then present the results obtained from the Questionnaire sur l'éducation à la carrière, completed by 1,022 students. These results include the existence or lack of significant differences between girls and bovs regarding their work values, their relative attitudes towards their career planning and professional exploration, and their knowledge of the work force. Some guidance specific to girls are drawn.